STUDY CLINICAL, RADIOLOGICAL, ELECTROCARDIOGRAPHIC, AND ECHOCARDIOGRAPHIC CHANGES IN CHRONIC CORPULMONALE - NAGWANSHI, JYOTI; GATHORIA, MANISH; HARINKHEDE, ANITA; RANGARE, VIKAS (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: Chronic cor pulmonale accounts for 5–10% of all heart diseases and 20–30% of all admissions for heart failure. The development of pulmonary hypertension (PAH) and subsequent chronic cor pulmonale increases the risk of hospitalization and is associated with reduced survival. Echocardiography examination can quantify the extent of the right ventricular hypertrophy (RVH) and PAH noninvasively. Methods: This is a prospective and observational study conducted in 74 included cases admitted in the department of general medicine, NSCB Medical College Hospital, Jabalpur. On the basis of patient’s history, physical findings, radiological findings, and electrographic changes, the diagnosis of chronic cor pulmonale was made and was subjected to echocardiography examination. Results: Cor pulmonale was more common in smokers with male-to-female ratio of 2.52:1 and was more common in the 4th, 5th, and 6th decade of life. ECGshowed 58.10% of cases with RVH, 59.45% with right axis deviation, 48.64% right bundle branch block, and 66.21% with P pulmonale. Echocardiographic evaluation revealed right ventricular dilatation in 100% cases, RVH in 94%, tricuspid regurgitation in 52.70%, right atrial enlargement in 50%, PAH in 97.29%, diastolic septal flattening in 16.21%, paradoxical motion of the IV septum in 8.1%, reduced left ventricular end-diastolic volume in 8.1%, and left ventricular ejection fraction reduced in 22.97%. Conclusion: Detection of chronic cor pulmonale in the early stage is important for therapeutic and prognostic implication. Echocardiography is a non-invasive, affordable investigation for early diagnosis of chronic cor pulmonale.